Optimal design of ultra‐broadband, omnidirectional, and polarization‐insensitive amorphous silicon solar cells with a core‐shell nanograting structure. (18th April 2012) - Yang, L.; Mo, L.; Okuno, Y.; He, S.
ABSTRACT We systematically investigated the optical behaviors of an amorphous silicon solar cell with a core‐shell nanograting structure. The horizontally propagating Bloch waves and Surface Plasmon Polariton waves lead to significant absorption enhancements and consequently short‐circuit current enhancements of this structure, compared with the conventional planar one. The perpendicular carrier collection makes this structure optically thick and electronically thin. An optimal design is achieved through full‐field numerical simulation, and a physical explanation is given. Our numerical results show that this configuration has ultra‐broadband, omnidirectional, and polarization‐insensitive responses and has a great potential in photovoltaics. Copyright © 2012 John Wiley & Sons, Ltd.